The Mystery In Arabic Rhetoric, Its Eloquence And Images - Faisal Mohmmed Alasiry (Ijaz Arabi Journal of Arabic Learning, 2023)
Mystery, mystification, puns, and metonymy are all examples of rhetoric. They convey the meaning in different ways from that of the disclosure. It was found that mystery in Arabic rhetoric includes ambiguity. So, the study focuses on the forms of ambiguity in Arabic rhetoric in two topics: the first deals with two meanings and one word, while the second deals with two words and two definitions. The inductive method was used following the references of rhetoricians. And the analytical method when dealing with the evidence of ambiguity in the rhetorical lesson. Therefore, the research dealt with several forms of mystery in Arabic rhetoric, which intends the mastery of the methods and forms of speech. The results show the diversity of mystery images and the breadth of their meaning with several mystery forms in Arabic rhetoric. The study shows that means of Arabs flip the words away. Diversify the connotation,  expands the knowledge, and indicate the methods of Arabs in expressing something, including hidden meanings, which are called puns. This research can help Arabic language learners understand the importance and hidden meanings of Allegory and what the book's author means. Knowledge of the Arabic language methods of metaphorical transcript and its characteristics change the meaning or evolution of the Arabic language.